2016
DOI: 10.1038/ejcn.2016.201
|View full text |Cite
|
Sign up to set email alerts
|

The effects of partial sleep deprivation on energy balance: a systematic review and meta-analysis

Abstract: The pooled effects of the studies with extractable data indicated that PSD resulted in increased EI with no effect on EE, leading to a net positive energy balance, which in the long term may contribute to weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 53 publications
13
111
1
2
Order By: Relevance
“…However, when controlling for BMI, analyses showed that after the sleep deprivation, good sleepers with higher BMI consumed more kcal. Consistently, previous literature indicated that partial sleep deprivation increased food intake in healthy participants (Al Khatib, Harding, Darzi, & Pot, 2017), although the role of BMI remained understudied.…”
Section: Discussionsupporting
confidence: 75%
“…However, when controlling for BMI, analyses showed that after the sleep deprivation, good sleepers with higher BMI consumed more kcal. Consistently, previous literature indicated that partial sleep deprivation increased food intake in healthy participants (Al Khatib, Harding, Darzi, & Pot, 2017), although the role of BMI remained understudied.…”
Section: Discussionsupporting
confidence: 75%
“…This increased consumption of energy (via food/drink) [9] exceeds the additional energy required to sustain the extended wakefulness associated with either type of sleep loss [1,15,16,17]. Notably, the additional energy cost differs by sleep loss type: approximately 100 additional calories are required during sleep restriction [1,15], while 135 additional calories are required during total sleep deprivation [16], suggesting that intake amounts may differ during and following these sleep loss types to compensate for differential increases in energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…), and factors related to time and duration of working hours may contribute to food choice; for example, sleep duration (Al Khatib et al . ), job strain (Clark et al . ) and socioeconomic status (Bolton‐Smith et al .…”
Section: The Methodological Challenges Of Investigating Diet and Workmentioning
confidence: 99%